3D MRI of impaired hyperpolarized 129Xe uptake in a rat model of pulmonary fibrosis. (12th May 2014) - Cleveland, Zackary I.; Virgincar, Rohan S.; Qi, Yi; Robertson, Scott H.; Degan, Simone; Driehuys, Bastiaan; Rizi, Rahim R.
<x xml:space="preserve">Abstract</x> A variety of pulmonary pathologies, in particular interstitial lung diseases, are characterized by thickening of the pulmonary blood–gas barrier, and this thickening results in reduced gas exchange. Such diffusive impairment is challenging to quantify spatially, because the distributions of the metabolically relevant gases (CO2 and O2) cannot be detected directly within the lungs. Hyperpolarized (HP) 129Xe is a promising surrogate for these metabolic gases, because MR spectroscopy and imaging allow gaseous alveolar 129Xe to be detected separately from 129Xe dissolved in the red blood cells (RBCs) and the adjacent tissues, which comprise blood plasma and lung interstitium. Because 129Xe reaches the RBCs by diffusing across the same barrier tissues (blood plasma and interstitium) as O2, barrier thickening will delay 129Xe transit and, thus, reduce RBC‐specific 129Xe MR signal. Here we have exploited these properties to generate 3D, MR images of 129Xe uptake by the RBCs in two groups of rats. In the experimental group, unilateral fibrotic injury was generated prior to imaging by instilling bleomycin into one lung. In the control group, a unilateral sham instillation of saline was performed. Uptake of 129Xe by the RBCs, quantified as the fraction of RBC signal relative to total dissolved 129Xe signal, was significantly reduced (P = 0.03) in the injured lungs of bleomycin‐treated animals. In contrast, no significant difference (P = 0.56) was observed between the saline‐treated and untreated lungs of control animals. Together, these results indicate that 3D MRI of HP 129Xe dissolved in the pulmonary tissues can provide useful biomarkers of impaired diffusive gas exchange resulting from fibrotic thickening. Copyright © 2014 John Wiley & Sons, Ltd.